117 Medicines optimisation before discharge in patients admitted to hospital with heart failure. (6th June 2022) - Cuthbert, Joe; Brown, Oliver; Pellicori, Pierpaolo; Dobbs, Karen; Bulemfu, Jeanne; Kazmi, Syed; Sokoreli, Ioanna; Pauws, Steffen; Riistama, Jarno; Cleland, John; Clark, Andrew
Abstract : Background: In the UK, approximately half of patients with heart failure and a reduced ejection fraction (HeFREF) are discharged from hospital on triple therapy (angiotensin converting enzyme inhibitors (ACEI) or angiotensin receptor blockers (ARB), beta-blockers (BB), and mineralocorticoid receptor antagonists (MRA). It is unknown what proportion of patients would be eligible for uptitration of medicines prior to discharge, nor how many might be eligible for initiation of sacubitril-valsartan or sodium-glucose co-transporter-2 inhibitors (SGLT2I). Methods: Between 2012 and 2017, 1, 277 patients admitted with suspected heart failure were enrolled at a single hospital serving a local community around Kingston-Upon-Hull, UK. Eligibility for sacubitril-valsartan or SGLT2I was based on entry criteria for the PIONEER-HF, DAPA-HF and EMPEROR-Reduced trials. Results: 455 patients had HeFREF with complete data on renal function, heart rate and systolic blood pressure (SBP) on discharge. 83% were taking an ACEI/ARB, 85% a BB and 63% MRA on discharge (figure 1). More than 60% were eligible for sacubitril-valsartan and more than 70% for SGLT2i (figure 2). Among those not already receiving a each drug, 37%, 28%, and 49% were eligible to start ACEI/ARB, BB, or MRA respectively (tables 1 and 2). Low SBP (<105 mmHg) was the most common reason for failure to initiate or up-titrate (table 2). Conclusion: Most patients admitted for heart failure are eligible for initiation of life prolonging medications prior to discharge. A hospital admission may be a common missed opportunity to improve treatment for HeFREF. Conflict of Interest: none